EXPERIMENTS FOR THE PRODUCTION OF NON-FERROUS METALS FROM CONVERTER DUST - Mamarakhimov , Safarali Kamolidinovich; Eshmuhamedov , Sodikjon Obidjonugli; Turdiev , Abboskhon Bakhtiyorugli (Sanoatda raqamli texnologiyalar, 2024)
The results presented show the production of lead from dusts generated during the purification of outgoing gas during the conversion process of a copper smelter. A technology has been developed to study the chemical composition of converter dust and determine its initial and physical properties during its processing. According to the proposed technology, zinc and copper are first transferred into solution by sulfuric acid leaching. From the remaining cake, the lead is first transferred to a brine solution and then the carbonation is precipitated as lead carbonate, which is calcined and melted in a reducing environment to produce metallic lead.